Monitoring harian pesawat linac dengan EPID: studi pendahuluan - Andrian Dede Handika; Sugiyantari Sugiyantari (Journal of Medical Physics and Biophysics, 2019)
Took place in Persahabatan Hospital, Department of Radiotherapy, a research has been held using Linac Elekta Precise equipped by EPID (Electronic Portal Imaging Device). The research is focused on daily measurement on Linac using EPID and Ionization Chamber which the results were compared in effort to use EPID as alternative detector for daily measurement on Linac. The Linac Elekta Precise used in this research was equipped with EPID iViewGT a-Si flat panel with energy consist of 6 MV and 10 MV, 160 cm SDD (Source to Detector Distance), MU variations between 95-105 MU with 1 MU interval, and measured on 10 cm x 10 cm for the field size. Linac’s daily consistent measurement was held with 100 MU exposure and similar Linac’s parameter every day. EPID’s image beam profile evaluation was held along inplane and crossplane axis. The result is EPID’s calibration show a linear relation between pixel value and MU for both of energy beam (6 MV and 10 MV). Specifically, for Linac’s daily consistent measurement with 100 MU, the result show 3% deviation rate in general for both of energy beam which similar with Ionization Chamber measurement result. Flatness and symmetry that acquired from EPID’s image profile show no more than 2% deviation rate which still in tolerance limit. In conclusion, EPID’s daily image profile evaluation which covered output consistency, flatness, and symmetry beam profile show that EPID could be used for alternative detector for daily beam profile monitoring.